Colocasia esculenta L. Extract Increase Growth and Motility of Rotenone Induced Zebrafish (Danio rerio) Larvae Stunting Model - Furqon, Muhammad; Kumala, Shirly; Farida, Yunahara; Zaidan, Sarah; Sumiyati, Yati (Bioscientist : Jurnal Ilmiah Biologi, 2024)
This study aims to determine the effect of Colocasia esculenta L on the growth and motility of zebrafish (Danio rerio) larvae after induction of rotenone as a stunting model. The Zebrafish have divided 3 groups i.e Normal (embryonic medium without rotenone induction), Negative Control (embryonic medium with rotenone induction), and Treatment Groups (embryonic medium with rotenone induction and Colocasia esculenta extracts, dose 30-60-90 ppm). The stunting model is designed by induction of 12.5 ppb rotenone to Zebrafish larvae. The growth of the larvae was observed by using a microscope to measure the body and head length. Evaluation of motility was carried out by recording the movement of the fish for 1 minute, and the pace was analyzed by using Video Tracker. The evaluations were observed at 3, 6, 9 dpf (day post-fertilization). Colocasia Esculenta Extract (CEE) groups have higher body lengths compared to the Negative Control Group. The lengths were 125.4 µm for CEE30, 119.4 µm for CEE60, and 121.4 µm CEE90 while the length for the Negative Control Group was 118.3 µm at 9 dpf. However, there were no different values for the ratio of head length to body length of all groups. The ratio was 1:6 at 3 dpf, and 1:4 at 6 and 9 dpf. Moreover, the motility was higher in CEE groups compared to the Negative Control at 3, 6, 9 dpf. The body length and motility of Zebrafish larvae higher compare to the Negative Control Group showing the potential of Colocasia esculenta extract on growth and enhancement of motoric activity.